The Economics of Child Labor - Basu, Kaushik; Van, Pham Hoang (American Economic Review, 1998)
If child labor as a mass phenomenon occurs not because of parental selfishness but because of the parents' concern for the household's survival, the popular argument for banning child labor loses much of its force. However, this assumption about parental decision-making coupled with the assumption of substitutability in production between child and adult labor could result in multiple equilibria in the labor market, with one equilibrium where children work and another where adult wage is high and children do not work. The paper establishes this result and discusses its policy implications.